Atomic Force Microscopy Study of Atherosclerosis Progression in Arterial Walls. (4th February 2016) - Timashev, Peter S.; Kotova, Svetlana L.; Belkova, Galina V.; Gubar'kova, Ekaterina V.; Timofeeva, Lidia B.; Gladkova, Natalia D.; Solovieva, Anna B.
Abstract: Cardiovascular disease remains the leading cause of mortality worldwide. Here we suggest a novel approach for tracking atherosclerosis progression based on the use of atomic force microscopy (AFM). Using AFM, we studied cross-sections of coronary arteries with the following types of lesions: Type II—thickened intima; Type III—thickened intima with a lipid streak; Type IV—fibrotic layer over a lipid core; Type Va—unstable fibrotic layer over a lipid core; Type Vc—very thick fibrotic layer. AFM imaging revealed that the fibrotic layer of an atherosclerotic plaque is represented by a basket-weave network of collagen fibers and a subscale network of fibrils that become looser with atherosclerosis progression. In an unstable plaque (Type Va), packing of the collagen fibers and fibrils becomes even less uniform than that at the previous stages, while a stable fibrotic plaque (Vc) has significantly tighter packing. Such alterations of the collagen network morphology apparently, led to deterioration of the Type Va plaque mechanical properties, that, in turn, resulted in its instability and propensity to rupture. Thus, AFM may serve as a useful tool for tracking atherosclerosis progression in the arterial wall tissue.